Implementasi Pembelajaran pada Kursus Komputer Program Profesional Office di LPK Alfabank Semarang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of the Professional Office computer course learning program at LPK Alfabank, Semarang City. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that the implementation process involves three main stages: planning, execution, and evaluation. Planning was conducted through intensive coordination among administrators, instructors, and relevant parties, covering material preparation, teaching methods, media, and evaluation strategies. Learning execution emphasized a balance between theory (30%) and practice (70%), utilizing lectures, hands-on practice, discussions, and demonstrations. Evaluation was carried out through process and outcome evaluations, including observation, pre-tests, and post-tests to assess participants’ competency achievements. Supporting factors for successful learning included instructor competence, availability of learning media, and active participant engagement, while inhibiting factors involved software updates, unfavorable weather, and participant tardiness. These findings highlight that an effective implementation strategy in computer courses can enhance participants' competencies and better prepare them for workforce challenges.